Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1118/1.3633905
|View full text |Cite
|
Sign up to set email alerts
|

On the orientation of mammographic structure

Abstract: Purpose: Burgess et al. have shown that the power-spectral density of mammographic breast tissue P(f) follows a power-law, P(f) ¼ c=f b . 1 Due to the complexity of the breast anatomy, breast phantoms often make use of power-law backgrounds to approximate the irregular texture of breast images. However, the current methodology of estimating power-law coefficients assumes that the breast structure is isotropic. The purpose of this letter is to demonstrate that breast anatomic structure is not isotropic, but in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
(15 reference statements)
0
19
0
Order By: Relevance
“…Our previous studies have shown that mammographic power-spectra are not radially symmetric, but exhibit elliptical symmetry caused by the “directionality” of fibroglandular tissues, which tend to radiate towards the nipple (Reiser et al, 2011). The PWO is sensitive to this symmetry, which causes a performance difference between the two background types that can be observed for larger signals.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that mammographic power-spectra are not radially symmetric, but exhibit elliptical symmetry caused by the “directionality” of fibroglandular tissues, which tend to radiate towards the nipple (Reiser et al, 2011). The PWO is sensitive to this symmetry, which causes a performance difference between the two background types that can be observed for larger signals.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the effect of oriented ductal structures in sagittal and axial views, which do not as effectively mask the spherical simulated mass. 37 We note that, for thin sections typically used by the radiologist on the breast CT workstation, 25 the performance differences between views were relatively small.…”
Section: Ivb View Orientationmentioning
confidence: 99%
“…26 However, in the literatures, 22,27,28 the reported b is the result of the radial averaged power spectrum by WOAP with many small ROIs. This would be problematic if the assumption of an isotropic mammogram is not true.…”
Section: Discussionmentioning
confidence: 96%